Analyzing the Translation Strategies from the Perspective of Distanciation: A Case Study of Chinese National Defense Discourse - Xu, Yuemin (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This study analyzes the translation of Chinese national defense discourse from the perspective of Distanciation Theory (DT), integrating Wieczorek’s framework with Cap’s Proximizaiton Theory (PT) to propose the Spatial-Temporal-Axiological Distanciation (STAD) model. Using China’s National Defense in the New Era and Ministry of National Defense press conference transcripts as the corpus, it examines how spatial, temporal, and axiological Distanciation strategies in the source text are represented or modified in the target text. The analysis reveals that TT often amplifies Distanciation effects through “shift” and “free” translation, while “literal” translation effectively preserves ST strategies; in contrast, “omission” or certain “free” translations may weaken them. Findings demonstrate the STAD model’s explanatory power in identifying symbolic distance adjustments in translation and highlight the translator’s role in shaping discourse effects. The study underscores DT’s applicability to translation studies and suggests integrating PT and DT to refine theoretical and practical guidelines for translation practice.